Analisis Good Corporate Governance dan Karakteristik Perusahaan Terhadap Pengungkapan Corporate Social Responsibility - Elsa Sabrina Agustia; Tantina Haryati (IPM2KPE, 2023)
This research aims to study how corporate governance and company characteristics influence corporate social responsibility disclosure. There are many components that form effective corporate governance, including independent commissioners, audit committee, managerial ownership, board of directors, profitability and leverage. The population of this research is food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange during the 2017-2021 research period. The sample determination process used purposive sampling, obtaining 40 samples with a period of 5 years. The research results show that the audit committee and managerial ownership variables influence CSR disclosure. Meanwhile, the variables independent commissioner, board of directors, profitability and leverage have no effect on CSR disclosure. Keywords: Good Corporate Governance (GCG), Corporate Social Responsibility (CSR)